Christian-Jewish relations, 1000 - 1300: jews in the service of medieval christendom - Sapir Abulafia, Anna (The medieval world, 2011)
Pt. 1. The antecedents of Jewish service. 1. Augustine and Roman law -- 2. Gregory the Great and canon law -- Pt. 2. The political and socio-economic realities of Jewish service. 3. The Jews of Germany -- 4. The Jews of France -- 5. The Jews of England -- 6. The Jews of the Latin Mediterranean -- Pt. 3. The religious and cultural ambiguities of Jewish service. 7. Jewish experience of the crusades -- 8. Anti-Jewish libels -- 9. Conclusion: Jewish service in encounters between Christians and Jews